2018
DOI: 10.1016/j.jacc.2018.01.060
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Stress Kinase JNK in Binge Alcohol-Evoked Atrial Arrhythmia

Abstract: BACKGROUND Excessive binge alcohol drinking has acute cardiac arrhythmogenic effects, including promotion of atrial fibrillation (AF), which underlies “Holiday Heart Syndrome.” The mechanism that couples binge alcohol abuse with AF susceptibility remains unclear. We previously reported stress-activated c-Jun N-terminal kinase (JNK) signaling contributes to AF development. This is interesting because JNK is implicated in alcohol-caused organ malfunction beyond the heart. OBJECTIVES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 39 publications
4
80
0
Order By: Relevance
“…It was shown that GC stimulation results in increased ER stress, measured as reduced methylation of FK binding protein 51 (FKBP51) [60]. Importantly, increased ER stress has been linked to increased Ca spark activity and atrial fibrillation via increased phosphorylation and activation of CaMKIIδ in human, rabbit and mouse atrial tissue [62,63]. Moreover, direct stimulation of SOCE by high doses of 2-aminoethoxydiphenyl borate (2-APB; 20 μM) has been shown to induce arrhythmias and spontaneous contractions in an Orai-dependent fashion in rat atrial and ventricular myocytes [64].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that GC stimulation results in increased ER stress, measured as reduced methylation of FK binding protein 51 (FKBP51) [60]. Importantly, increased ER stress has been linked to increased Ca spark activity and atrial fibrillation via increased phosphorylation and activation of CaMKIIδ in human, rabbit and mouse atrial tissue [62,63]. Moreover, direct stimulation of SOCE by high doses of 2-aminoethoxydiphenyl borate (2-APB; 20 μM) has been shown to induce arrhythmias and spontaneous contractions in an Orai-dependent fashion in rat atrial and ventricular myocytes [64].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are other promising approaches in terms of research of the JNK role in alcohol drinking. Yang et al showed an interesting insight into the development of alcohol-induced liver steatosis and the involvement of cytochrome P4502E1 and JNK activation [ 45 ], while Yan et al underlined the possible role of JNK in the binge drinking-related progression of atrial arrhythmia in the holiday heart syndrome [ 46 ]. Further research on the JNK role in chronic inflammatory diseases should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ethanol or acetaldehyde (a byproduct of ethanol) can lead to abnormal concentrations of intracellular Ca 2+ [26]. Therefore, alcohol exposure activates stress kinases in atrial myocytes thereby prompting aberrant Ca 2+ waves which results in increased susceptibility to atrial arrhythmias [27].…”
Section: Discussionmentioning
confidence: 99%